Hematogenous Dissemination of Breast Cancer Cells From Lymph Nodes Is Mediated by Tumor MicroEnvironment of Metastasis Doorways - Coste, Anouchka; Karagiannis, George S.; Wang, Yarong; Xue, Emily A.; Lin, Yu; Skobe, Mihaela; Jones, Joan G.; Oktay, Maja H.; Condeelis, John S.; Entenberg, David (Frontiers in Oncology, 2020)
In primary breast tumors, cancer cells hematogenously disseminate through doorways in the vasculature composed of three-cell complexes (known as Tumor MicroEnvironment of Metastasis) comprising a perivascular macrophage, a tumor cell overexpressing the actin-regulatory protein Mammalian Enabled (Mena), and an endothelial cell, all in direct physical contact. It has been previously shown that once tumor cells establish lymph node metastases in patients, TMEM doorways form in the metastatic tumor cell nests. However, it has not been established if such lymph node-TMEM doorways actively transit tumor cells into the peripheral circulation and on to tertiary sites. To address this question in this short report, we used a mouse model of lymph node metastasis to demonstrate that TMEM doorways: 1) exist in tumor-positive lymph nodes of mice, 2) are restricted to the blood vascular endothelium, 3) serve as a mechanism for further dissemination to peripheral sites such as to the lungs, and 4) their activity can be abrogated by a pharmaceutical intervention. Our data suggest that cancer cell dissemination via TMEM door-ways is a common mechanism of breast cancer cell dissemination to distant sites and thus the pharmacological targeting of TMEM may be necessary, even after resection of the primary tumor, to suppress cancer cell dissemination.